2018
DOI: 10.1155/2018/4047682
|View full text |Cite
|
Sign up to set email alerts
|

An Association Rule Based Method to Integrate Metro-Public Bicycle Smart Card Data for Trip Chain Analysis

Abstract: Smart card data provide valuable insights and massive samples for enhancing the understanding of transfer behavior between metro and public bicycle. However, smart cards for metro and public bicycle are often issued and managed by independent companies and this results in the same commuter having different identity tags in the metro and public bicycle smart card systems. The primary objective of this study is to develop a data fusion methodology for matching metro and public bicycle smart cards for the same co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 31 publications
(46 reference statements)
0
13
0
Order By: Relevance
“…Based on this, multi-ring buffers were created at the 409 metro entrances in ArcGIS. Generally, 300 m is used as the maximum transfer distance for public bike to access/egress metro stations [35][36][37]. Considering that individuals can pick up or drop off free-floating shared bikes close to the metro stations, a total of 25 buffers were constructed from 0 m to 250 m at an interval of 10 m for each metro entrance.…”
Section: Before Designing the Questionnairementioning
confidence: 99%
“…Based on this, multi-ring buffers were created at the 409 metro entrances in ArcGIS. Generally, 300 m is used as the maximum transfer distance for public bike to access/egress metro stations [35][36][37]. Considering that individuals can pick up or drop off free-floating shared bikes close to the metro stations, a total of 25 buffers were constructed from 0 m to 250 m at an interval of 10 m for each metro entrance.…”
Section: Before Designing the Questionnairementioning
confidence: 99%
“…Ma et al [36] analyzed the distribution of bikeshare travel distance and travel time of metro-bikeshare users and found that the main function of bikeshare integrated with the metro is commuting, rather than entertainment or exercising. In addition, in Zhao's [37] study, some interesting findings of metro-bikeshare transfer were derived; for instance, the first-mile trips during the morning peak had the same spatial pattern as the last-mile trips during the evening peak. Also, the distance of the first-mile or last-mile bikeshare trips was shorter than that of the other bikeshare trips.…”
Section: Travel Characteristics Of Metro-bikeshare Integrationmentioning
confidence: 99%
“…The Stations profile includes station ID, station name, and the longitude/latitude of the docking station. We applied two matching rules to recognize metro-bikeshare transfer trips: a maximum transfer time of 10 min and a maximum transfer distance of 300 m [37,43]. After applying the two rules of maximum travel time and distance, 12,331 metro-bikeshare transfer trips made by 3836 passengers at 39 transfer pairs were generated.…”
Section: Dependent Variable: Activity Space Of Bikeshare Around the Mmentioning
confidence: 99%
See 1 more Smart Citation
“…For urban transit system operation at the bus stop, transport infrastructure geometry patterns [15, 16], traffic flow characteristics [17–19], and driver behaviour [20–22] near bus stop are analysed for modelling the travelling time [23–26], dwelling time [27–29], arrival pattern [30, 31], bunching characteristics [32, 33], capacity, and level of service (LOS) [34, 35]. They are modelled through different kinds of data such as automated vehicle location (AVL) data [36, 37] and smart card data [37–39]. Transit travelling delay occurred at the downstream signalised intersection is usually shorter than upstream of it [15], therefore, the impact of near‐side bus stop should be drawn more attention.…”
Section: Introductionmentioning
confidence: 99%